Positioning public nursing colleges in South African higher education: Stakeholders' perspectives - Zanele P. Zwane; Ntombifikile G. Mtshali (AOSIS, 2019)
Background: Public nursing colleges (PNCs) are currently redeploying from provincial departments of health to higher education to become part of a unified higher education system in South Africa. As primary producers of nurses, this migration process needs to be managed carefully, with stakeholders having a common understanding of this process. Objectives: This study aimed to explore the stakeholders' perspectives on the positioning of PNCs in higher education. Method: The study followed a qualitative grounded theory design. Purposive and theoretical sampling were utilised to achieve a sample size of 40 participants, including representatives from the Department of Higher Education and Training; professional associates; nursing educators; student leaders; nursing leaders; and nurses from the healthcare setting. Data were collected through observations, interviews and document analysis. Results: It emerged from the study that the integration of PNCs into higher education is a result of the country's political and legal context. A number of policy and legal frameworks emerged as contextual conditions that provided a basis for the change. The integration of PNCs into higher education was conceptualised as a functional shift in the governance of colleges; a political tool to transform nursing education; a means to enhance the quality of college-based nursing programmes, and a vehicle for the greater professionalisation of nursing. Conflicting legislation and funding emerged as two issues of concern. Conclusion: Integrating PNCs with higher education came about because of political changes and the resolution of the ruling party to improve the quality of graduates produced, who will in turn improve the quality of healthcare service delivery offered.